2016
DOI: 10.1177/1557988315584794
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Education, Detection, and Follow-Up in a Community-Based Multiethnic Cohort of Medically Underserved Men

Abstract: The Prostate Outreach Project (POP) provided free prostate cancer (PCa) education and early detection to medically underserved communities. POP recruited subjects in medically underserved communities. PCa education and detection events occurred in POP locations (static) or natural gathering places (mobile) within the community. PCa education was delivered by video and evaluated using a questionnaire. Screening consisted of serum prostate specific antigen (PSA) and digital rectal examination (DRE). A navigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 33 publications
2
19
1
Order By: Relevance
“…In our cohort, 33.1% of participants had adequate baseline knowledge, and this rate increased to 77% after the presentation. Increased knowledge on PCa screening after a DA has been reported previously in several studies . The level of increase in PCa knowledge depends on many factors, such as baseline level of knowledge, educational status of the population, the type of DA (Web‐based, print, or presentation), and the content of the DA.…”
Section: Discussionmentioning
confidence: 63%
“…In our cohort, 33.1% of participants had adequate baseline knowledge, and this rate increased to 77% after the presentation. Increased knowledge on PCa screening after a DA has been reported previously in several studies . The level of increase in PCa knowledge depends on many factors, such as baseline level of knowledge, educational status of the population, the type of DA (Web‐based, print, or presentation), and the content of the DA.…”
Section: Discussionmentioning
confidence: 63%
“…This finding has prompted us to study other potential confounders since the AA controls were recruited from community settings in Houston while the cases were AA patients from the MDACC, a tertiary referral center for treatment of cancer. We have previously shown that subjects recruited in the Houston community study exhibited a lower socioeconomic (SES) status in terms of education, insurance, and having a regular physician . Freeman et al , directly correlated low SES with lower PCa survival and found that this was eliminated in equal access care settings .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that subjects recruited in the Houston community study exhibited a lower socioeconomic (SES) status in terms of education, insurance, and having a regular physician. 27 Freeman et al 33, directly correlated low SES with lower PCa survival and found that this was eliminated in equal access care settings. 33 evaluating other variables their group found that obesity was a significant predictor of aggressive PCa for the EA population more than the AA cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that a culturally tailored decision aid delivered in barbershops led to significantly more men intending to have a prostate-specific antigen (PSA) test after a follow-up period of three months (Frencher et al, 2015). Another study using PCa screening events in medically underserved communities in Houston, Texas reported over half of the men had no prior history of screening (Ashorobi et al, 2015). This article describes baseline survey findings from an efficacy study conducted with African-American barbershop clients in two micropolitan areas in central and southeast Georgia.…”
mentioning
confidence: 99%